Multiple enchondromas in Ollier's disease: A case report - Jeremy Hugh Yen-hey Lau, MBBS; Koon Kiu Ng, MBBS, FHKCR; Wai Chung Wong, MBBS, FHKCR; Boom Ting Kung, MBChB, FHKCR (Radiology Case Reports, 2024)
Ollier's disease is a rare sporadic nonhereditary condition associated with mutations in the IDH1 and IDH2 genes, that manifests in early age of life. It is characterized by widespread enchondromas, predominantly affecting one side of the body. Diagnosis is based on clinical and radiological evaluations, and interval assessment for Ollier's disease is important as enchondromas are at risk of malignant transformation into chondrosarcomas. This case report aims to discuss the role of bone scan and plain X-ray in managing multiple enchondromas of a 25-year-old male patient with swellings over the left chest wall and left acromial regions.